2003
DOI: 10.1002/jmv.10359
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus C epidemiology in denmark: Different routes of transmission in children and low‐ and high‐risk adults

Abstract: With the demonstration of an effect of GBV-C infection on the outcome of HIV infection, it has become important to understand the epidemiology of GBV-C. The purpose of this study was to determine the prevalence in high- and low-risk populations. The following populations were tested: school children, 9 and 15 years of age (n = 901), blood donors (n = 5,203), hospital employees (n = 1,432), and prisoners and injecting drug users (n = 447). In-house RT-PCR for GBV-CRNA was used together with a commercial ELISA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
4
20
0
Order By: Relevance
“…HBV DNA was not screened in liver samples (which can often be present despite negativity in blood [25]) because of technical limitations and the uncertainties regarding the physiopathological relevance of positive liver HBV DNA in association without blood replication. The prevalence of GBV-C infection in HIV-HCV coinfected patients in our study and in two others [26,27] was 30-36%, which is close to that observed in IVDUs (39-45% [28,29]) and higher than that reported in studies mainly including homosexual men (14-37% [30,31]). The prevalence we observed may have been slightly underestimated since only one pair of primers was used instead of the two recommended by others [32].…”
Section: Discussionsupporting
confidence: 86%
“…HBV DNA was not screened in liver samples (which can often be present despite negativity in blood [25]) because of technical limitations and the uncertainties regarding the physiopathological relevance of positive liver HBV DNA in association without blood replication. The prevalence of GBV-C infection in HIV-HCV coinfected patients in our study and in two others [26,27] was 30-36%, which is close to that observed in IVDUs (39-45% [28,29]) and higher than that reported in studies mainly including homosexual men (14-37% [30,31]). The prevalence we observed may have been slightly underestimated since only one pair of primers was used instead of the two recommended by others [32].…”
Section: Discussionsupporting
confidence: 86%
“…As IDU and having tattoos were associated with the highest odds of GBV-C infection, parenteral transmission may be more efficient than sexual transmission. Since there were only 25 IDUs in our cohort (<2% of study subjects), all of whom were HIV-infected, this risk estimate may be somewhat unstable, but was similar to that observed in other cohorts [Christensen et al, 2003]. However, sexual risk behaviors were more common than parenteral risks in our study population, and a high proportion of women in high sexual risk categories were also GBV-C infected, including commercial sex workers, women reporting more than 10 lifetime sexual partners, and women reporting first intercourse at <15 years of age.…”
Section: Discussionsupporting
confidence: 81%
“…Studies of the prevalence and correlates of GBV-C infection among different populations have identified many risk factors for GBV-C infection, including, IDU [Katayama et al, 1997;Saganuma et al, 1998;Tan et al, 1999;Lefrere et al, 1999a;Christensen et al, 2003;Vanhems et al, 2003], receipt of blood transfusion [Stark et al, 1999;Tan et al, 1999;Henrichsen et al, 2002], increased number of sexual partners [Wu et al, 1997;Bjorkman et al, 2001;Ribeiro-dos-Santos et al, 2002], having had sex with other men [Stark et al, 1999;Lefrere et al, 1999a;Rey et al, 2000;Berzsenyi et al, 2005], snorting cocaine [Tan et al, 1999], imprisonment [Tan et al, 1999], history of sexually transmitted infections (STIs) [Tan et al, 1999;Bjorkman et al, 2001], healthcare work [Christensen et al, 2003], hospitalization for medical procedures such as delivery and abortion [Lefrere et al, 1999a], endoscopy [Bjorkman et al, 2001], and bronchoscopy [Vanhems et al, 2003], as well as a history of travel to Africa [Lefrere et al, 1999a], schistosomiasis [Hassoba et al, 1997], and exposure to blood-sucking insects [Ribeiro-dos-Santos et al, 2002]. Using a study cohort of 1,387 HIV-infected and 332 HIV-uninfected pregnant women drawn from three perinatal studies in Bangkok, associations between GBV-C RNA and antibody prevalence with demographic, medical, and risk behavior variables were examined to determine the risk factors for GBV-C infection and clearance.…”
mentioning
confidence: 99%
“…Unfortunately, we were not able to test the mothers to confirm perinatal transmission. Besides, other transmission routes (i.e., sexual or through breast-feeding) for GBV-C infection that have been suggested [2] could not be ruled out either.…”
Section: Discussionmentioning
confidence: 93%